Factors Relating to Dark Heart and Internal Rate of Return of Sugar Maple in Wisconsin - Kaminski, Joel C. (University of Wisconsin-Stevens Point, College of Natural Resources, 2019)
Sugar maple (Acer saccharum) is a valuable tree species in the commercial lumber market in the United States. Internal discoloration of the heartwood (or dark heart) in sugar maple causes a significant degrade in the quality of the wood. While not necessarily harmful to the tree itself, stained maple boards sell for a significantly lower price in the lumber market when compared with white wood. Foresters often grade standing trees by observing external defects and grade each tree based on the products they might produce. However dark heart is considered an internal defect, which makes it difficult to observe the extent and impact it has on uncut trees. Our research addressed these issues by examining external tree characteristics and site factors that might predict the size and shape of the discoloration in standing trees. Over the course of two summers, we sampled 200 trees within 10 active logging sites and 74 trees within 8 active logging sites across central Wisconsin. Each tree sampled was measured before and after cutting. Data from each site (soil chemistry, geology, and habitat type) was collected along with individual tree observations and measurements [diameter at breast height (4.5 ft.), height, age, form class, grade, and notable external defects]. The heart size on each cut log was measured and classified based on shape and average size. Our results were split into two separate studies (Project 1 and Project 2) to examine different factors. The first study, which focused on the factors that affect heart size, found that smaller, faster growing trees with fewer defects have lower proportions of dark heart. Our second study also found that young stems with few defects had the highest internal rate of return over a 10 year period, which decreases as quality decreases and diameter increases.